The Effects of Vocabulary Mastery and Logical Thinking on Junior High School Students’ Listening Skill - Utami Rosalina; Dwi Nopiyadi; Siti Sahronih (Indonesian Journal of Multidisciplinary Science, 2021)
This research is aimed as follows: To get empirical data and analyze the effects of vocabulary mastery and logical thinking towards students’ listening skills at Junior High School in East Cirebon. This research is done by Kolmogorov-Smirnov method, ANOVA Table, Proportional Correct for testing the item difficulties, by a biserial coefficient, and by Kuder Richarsson testing. The research was held at Junior High School in East Cirebon. Data collective done by giving a test for listening skill (yes/no or true-false / 37 items), test for vocabulary mastery (Multiple choice/ 20 items), and test for logical thinking (multiple choice/20 items) given to the class at, SMP N 1 Ciledug, SMP N 1 Pabedilan, and SMP N 1 Losari. The result of the study identifies the effect of Vocabulary Mastery on Student’s Listening skills (coefficient of 0,745 and coefficient determination of 55,4%). The effect of logical thinking towards student’s listening skill (Sig = 0.031 and ttest = 2,183; while ttable = 1,98. There is an effect of vocabulary mastery and logical thinking on students’ listening skills (Sig = 0.000 and ttest = 4,757 while ttable = 1,98.).